Alternative supplemental feeding of Apis mellifera L. during the time of shortage in Yucatán, México - Tucuch Haas, Jorge Ismael; Rangel Fajardo, María Alma; Casanova Lugo, Fernando; Ruíz sánchez, Esaú; Utrera Quintana, Fernando; Tucuch Haas, Cesar Jacier; Burgos Díaz, Johnny Abraham (Ecosistemas y Recursos Agropecuarios, 2020)
Beekeeping is one of the outstanding activities worldwide, however, the time of shortage of nectar and pollen negatively affects the conditions of the colonies; In view of this situation, the present work aimed to evaluate protein syrups obtained from chaya leaves (Cnidoscolus aconitifolius Mill IM Johns), moringa (Moringa oleifera L.) and ramón seeds (Brosimum alicastrum Swarts) added in doses of 10, 25 and 50 g of sugar syrup in a 1: 1 ratio (p / v). Acceptance, weight gain, number of bees, number of cells with capped brood, nectar-honey and pollen were recorded. Data were collected using a completely randomized blocks design with a 3x4 factorial arrangement. The B. alicastrum syrup had an acceptance of 99.9%, followed by C. aconitifolius and M. oleifera, with 91.7 and 83.4% respectively, in weight gain, B. alicastrum gained 0.87 ± 0.14 kg, followed by C. aconitifolius and M. oleifera, with 0.3 ± 0.17 and -0.4 ± 0.11 kg respectively, in the same way B. alicastrum presented the best response for the variables, number of bees (1021.64), cells with brood (499.69) and cells with nectar. -Honey (515.22), surpassing C. aconitifolius (791.33 bees, 125.88 brood and 299.88 nectar-honey) and M. oleifera (805.08 bees, 240.11 brood and 305.45 nectar-honey); It is concluded that the syrup added with 25 g of B. alicastrum was the best combination and can be used as an efficient alternative in the supplementary feeding of honey bees during the lean season.